2016
DOI: 10.1002/anie.201510820
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed C−C Bond Cleavage of 2H‐Azirines: A Formal [3+2+2] Cycloaddition to Fused Azepine Skeletons

Abstract: 2H-azirines can serve as three-atom synthons by C-C bond cleavage, however, it involves a high energy barrier under thermal conditions (>50.0 kcal mol(-1) ). Reported is a ruthenium-catalyzed [3+2+2] cycloaddition reaction of 2H-azirines with diynes, thus leading to the formation of fused azepine skeletons. This approach features an unprecedented metal-catalyzed C-C bond cleavage of 2H-azirines at room temperature, and the challenging construction of aza-seven-membered rings from diynes. The results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 142 publications
0
27
0
Order By: Relevance
“…Our investigation showed that, upon sulfonylation of the oximes, only N ‐aryl carboxamidoximes ( 1 ) can undergo the intramolecular electrophilic aromatic substitution reaction to form the corresponding CN bond. In the absence of the amide nitrogen and the lack of a strong base in the reaction, heterolytic NO bond cleavage of ketoximes 4–6 predominantly triggered the subsequent CC bond dissociation between the oxime carbon and the neighborintg carbons to undergo Beckmann rearrangement or fragmentation reactions. We postulated that the amide nitrogen provided a resonance stabilization for the putative nitrene species formed after the heterolytic cleavage of the NO bond and allowed the electrophilic nitrogen to be captured by the N ‐aryl ring carbon.…”
Section: Methodsmentioning
confidence: 99%
“…Our investigation showed that, upon sulfonylation of the oximes, only N ‐aryl carboxamidoximes ( 1 ) can undergo the intramolecular electrophilic aromatic substitution reaction to form the corresponding CN bond. In the absence of the amide nitrogen and the lack of a strong base in the reaction, heterolytic NO bond cleavage of ketoximes 4–6 predominantly triggered the subsequent CC bond dissociation between the oxime carbon and the neighborintg carbons to undergo Beckmann rearrangement or fragmentation reactions. We postulated that the amide nitrogen provided a resonance stabilization for the putative nitrene species formed after the heterolytic cleavage of the NO bond and allowed the electrophilic nitrogen to be captured by the N ‐aryl ring carbon.…”
Section: Methodsmentioning
confidence: 99%
“…Wang, Wan, and co-workers reported a Ru-catalyzed [3+2+2]cycloaddition reaction of 2H-azirines with diynes leading to fused azepine skeletons (Scheme 13). 11 This transformation provides a facile and straightforward method for the formation of fused azepine derivatives, and features broad substrate scope and a wide range of functional groups. Notably, the C-C bond of the 2H-azirines was selective cleaved to achieve the tandem [5+2]-cycloaddition reaction.…”
Section: [3+2+2] Cycloadditionmentioning
confidence: 99%
“…The first report involving 2 H ‐azirines as 3π‐component in [3+2+2] cycloadditions is reported by Tengfei Li and co‐workers. It involves the ruthenium‐catalyzed [3+2+2] cycloaddition of diynes with 2 H ‐azirines under mild reaction conditions to construct seven‐membered fused azepine derivatives (Scheme , Figure ) …”
Section: Ruthenium‐catalyzed [3+2+2] Cycloaddition Reactions Of Azmentioning
confidence: 99%